Quality Analysis of South Sulawesi Bonto Matinggi Coal for Cement Industry Needs - Suriyanto Bakri; Imam Riswandi; Anshariah Anshariah; Harwan Harwan (PROMINE, 2022)
Coal in Indonesia is widely used for both export and domestic industrial needs. Domestically, it is widely used for the textile industry, power plants, and the cement industry. Coal consumption for the cement industry in Indonesia in 2022 is up to 15 million tons. In the cement industry, coal is used as a basic material for fuel in kilns. For its utilization, coal needs to know its properties. These properties can be known by proximate analysis, sulfur content analysis and calorific value. Therefore, this research aims to find out and determine whether the quality of Bonto Matinggi coal is in accordance with the coal specifications needed in the cement industry. The research method was carried out by taking two coal samples directly in the research area, namely SA I coal sample and SA II coal sample. The coal samples were then prepared and further analyzed. Analysis of coal sample quality was carried out by proximate, sulfur and calorie analysis methods. The results of proximate analysis show that the moisture content in air dried both samples have a value that is not too significant with an average value of 6.29% adb; ash content of 19.99% adb; volatile matter of 46.79% adb and fixed carbon of 39.86% adb as well as sulfur content of 0.39% adb and calories with an average of 4,692.92 cal/g. The coal in the study area does not qualify as a basic material for fuel in kilns in the cement industry. The coal in the study area, if classified according to the Classification of in Seam Coal 1998, is classified as low grade coal (according to ash content) and the coal rank includes bituminous rank (medium rank).